2006
DOI: 10.1016/j.neuron.2006.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Functional Maturation of CA1 Synapses Involves Activity-Dependent Loss of Tonic Kainate Receptor-Mediated Inhibition of Glutamate Release

Abstract: Early in development, excitatory synapses transmit with low efficacy, one mechanism for which is a low probability of transmitter release (Pr). However, little is known about the developmental mechanisms that control activity-dependent maturation of the presynaptic release. Here, we show that during early development, transmission at CA3-CA1 synapses is regulated by a high-affinity, G protein-dependent kainate receptor (KAR), which is endogenously activated by ambient glutamate. By tonically depressing glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
169
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(180 citation statements)
references
References 59 publications
11
169
0
Order By: Relevance
“…The results with the mGluR antagonist (S)-4-CPG suggest that activity in mGluR modulatory systems, perhaps activated by ambient glutamate, provide levels of IP3 sufficient to open intracellular stores. Tonic activation of KARs has been reported previously (Lauri et al, 2006) and is also seen with presynaptic NMDA receptors (Beretta and Jones, 1996;Corlew et al, 2007) In summary, it is suggested that following KAR activation, Ca 2+ enters through Ca 2+ permeable presynaptic GluR5 subunit containing KARs. This results in Ca 2+ release from intracellular stores through IP3Rs which produces an increase in inhibitory synaptic transmission.…”
Section: Involvement Of Ca 2+ and Ip3rssupporting
confidence: 54%
“…The results with the mGluR antagonist (S)-4-CPG suggest that activity in mGluR modulatory systems, perhaps activated by ambient glutamate, provide levels of IP3 sufficient to open intracellular stores. Tonic activation of KARs has been reported previously (Lauri et al, 2006) and is also seen with presynaptic NMDA receptors (Beretta and Jones, 1996;Corlew et al, 2007) In summary, it is suggested that following KAR activation, Ca 2+ enters through Ca 2+ permeable presynaptic GluR5 subunit containing KARs. This results in Ca 2+ release from intracellular stores through IP3Rs which produces an increase in inhibitory synaptic transmission.…”
Section: Involvement Of Ca 2+ and Ip3rssupporting
confidence: 54%
“…An indirect action involving thirdparty signaling molecules, like endocannabinoids, dopamine, adenosine (Chergui et al, 2000), or glutamate, is unlikely in view of the results obtained with the mixture of antagonists for various receptors including GABA-B, CB 1 , A 1 , D 4 , mGluRs, NMDA, nicotinic and ␣-2 adrenergic receptors. A direct action of KARs on transmitter release involving a G-protein-coupled signaling pathway has already been reported in other structures (Rodríguez-Moreno and Lerma, 1998;Cunha et al, 2000;Frerking et al, 2001;Lauri et al, 2005Lauri et al, , 2006Negrete-Diaz et al, 2006;Jin and Smith, 2007). This seems to be also the case in our recordings as indicated by the abolition of the KAR-mediated inhibitory effect in the presence of the PLC inhibitor, U73122.…”
Section: Coexistence Of Ionotropic and Metabotropic Kar Modes Of Actionsupporting
confidence: 88%
“…We first investigated indirect effects, including the activation of GABA-B autoreceptors (Kerchner et al, 2001) and other types of presynaptic receptors whose stimulation may take place in a retrograde (Chergui et al, 2000) This result argues against an indirect mechanism mediating the inhibitory effect of GluK1 activation on GABA release. We then investigated the possibility that the inhibitory action of GluK1 activation on GABA release depends on a direct coupling between KARs and transmitter release through a metabotropic G-protein pathway, a mechanism already described (Rodríguez-Moreno and Lerma, 1998;Cunha et al, 2000;Frerking et al, 2001;Lauri et al, 2005Lauri et al, , 2006Negrete-Diaz et al, 2006;Jin and Smith, 2007). To test for a similar mechanism in our recordings, we first tried to incubate hypothalamic slices for at least 5 h in the presence of pertussis toxin to block G-proteins.…”
Section: Mechanism Underlying Kar-mediated Inhibition Of Gaba Releasementioning
confidence: 97%
“…Although presynaptic kainate autoreceptors can increase facilitation at mossy fiber synapses in CA3 (e.g., Contractor et al, 2001), no such role had been described previously at any Schaffer collateral synapses. At Schaffer collateral synapses onto CA1 pyramidal cells, presynaptic kainate receptors instead depress glutamate release in response to high concentrations of exogenous agonists in juveniles (Frerking et al, 2001), or by tonic activation of high affinity receptors by ambient glutamate during the first postnatal week (Lauri et al, 2006). In juveniles, the depression of release occurs through low affinity receptors (Kamiya and Ozawa, 1998), whereas the facilitation of release at synapses onto EGFP-expressing SOM interneurons occurs via high-affinity receptors.…”
Section: Discussionmentioning
confidence: 99%